1999
DOI: 10.1126/science.285.5432.1375
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Crystallite Growth in the Sol-Gel Synthesis of Nanocrystalline Metal Oxides

Abstract: Crystal growth upon firing of hydrous transition metal oxide gels can be effectively inhibited by replacing the surface hydroxyl group before firing with another functional group that does not condense and that can produce small, secondary-phase particles that restrict advancing of grain boundaries at elevated temperatures. Accordingly, fully crystallized SnO(2), TiO(2), and ZrO(2) materials with mean crystallite sizes of approximately 20, 50, and 15 angstroms, respectively, were synthesized by replacing the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
271
1
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(285 citation statements)
references
References 8 publications
5
271
1
8
Order By: Relevance
“…So, There is also important significant for fuel cell and biosensor to study further electrocatalysis of CNTs/metal oxide or hydroxide composites. [216,217], while SnO 2 is sensitive to NOx, CO, ethanol, and C 2 H 4 [218]. However, their sensing properties often suffer degradation due to growth and aggregation.…”
Section: Electrocatalysismentioning
confidence: 99%
“…So, There is also important significant for fuel cell and biosensor to study further electrocatalysis of CNTs/metal oxide or hydroxide composites. [216,217], while SnO 2 is sensitive to NOx, CO, ethanol, and C 2 H 4 [218]. However, their sensing properties often suffer degradation due to growth and aggregation.…”
Section: Electrocatalysismentioning
confidence: 99%
“…Adding a secondary component as dopant or surface additive can dam the SnO 2 grain growth at calcination temperature 700 °C and improve the performance of SnO 2 gas sensors, especially for reducing gases (N.-L. Wu, Wang, & Rusakova, 1999;C. Xu, Tamaki, Miura, & Yamazoe, 1991).…”
Section: In 2 O 3 Gas Sensors For No X Detectingmentioning
confidence: 99%
“…Pang et al showed the size of SnO 2 nanoparticles could be controlled as small as 3.5 nm even heat treatment at 600°C [3]. Wu et al found that surface-modified methylsiloxyl groups on the metal oxide gel could prevent grain growth of metal oxides during high temperature treatments and excellent gas sensing properties were shown [4]. Lyu et al also showed that the thermal stabilities of mesoporous metal oxides were improved by introducing silicon-contained hybrid Gemini surfactants as a nano-propping agent [5].…”
Section: Introductionmentioning
confidence: 99%
“…In order to preserve nanostructured natures of materials at elevated temperatures, retardation of sintering behaviors was considered. However, only few reports emphasized stabilization of the nanostructured materials at high temperatures [1][2][3][4][5]. Pang et al showed the size of SnO 2 nanoparticles could be controlled as small as 3.5 nm even heat treatment at 600°C [3].…”
Section: Introductionmentioning
confidence: 99%